(untitled) (Annals of Medical Research, 2022)
Aim: Bell’s palsy (BP) pathogenesis is not fully understood, but is generally idiopathic. Studies investigating the etiopathogenesis of BP suggest have implicated factors such as inflammation, viral infection, microvascular dysfunction, and exposure to acute cold. The purpose of this study was to reveal the effectiveness of immature granulocyte (IG) as an inflammatory marker in the etiopathogenesis of BP. Materials and Methods: The retrospective study was performed September 2019 and January 2021. Thirty-three patients presenting to the our Ear, Nose, and Throat Clinic diagnosed with BP were included in the study. A control group consisting of 50 individuals with similar age and gender distributions to the patient group and presenting for routine examinations was also established. Immature granulocyte count (IGC), and immature granulocyte percentage (IG%) values were calculated from complete blood count (CBC) data. Results: No significant difference was determined between the two groups in terms of age or gender (p>0.05). IGC values found to differ significantly between the patient and control groups (p=0.004). No significant differences were observed in the IG% (p=0.061). Conclusion: Inflammation is one of the main theories in the context of BP. Higher IGC being determined in patients with BP compared to the healthy control group supports the idea of the role of inflammation in the etiopathogenesis.